Effect of the dopant on the structural and hyperfine parameters of Sn0.95M0.05O2 nanoparticles (M: V, Mn, Fe, Co) - Bilovol, Vitaliy (2019)
In this work, we present a comparative study of the structural and hyperfine parameters on tin dioxide nanoparticles doped with different transition metal elements. The nanopowders with the stoichiometry Sn0.95M0.05O2 (M: V, Mn, Fe, Co) were synthesized by simple co-precipitation method. The characterization was carried out by conventional x-ray diffraction technique, transmission 119Sn Mössbauer spectroscopy and x-ray photoelectron spectroscopy (XPS). The effect of dopant element on structural parameters of tin dioxide and, particularly, on hyperfine parameters of Sn was analysed. It was found that dopants, except for Fe, were in two valence states. For the Mn-doped SnO2 sample, it was found the strongest influence of M cation on Sn hyperfine parameters, whereas Co-doped sample resulted in the least altered one as compared to doped and un-doped SnO2. We propose an explanation of the changes of the hyperfine parameters observed over the modification of the structural changes, based on the size of the dopant elements, whose oxidation states were identified by XPS. Additionally, it should not be discarded the relevant role of oxygen vacancies whose presence on the surface was indirectly witnessed by XPS.